Serotonin Transporter Gene Polymorphisms and Early Parent-Infant Interactions Are Related to Adult Male Heart Rate Response to Female Crying - Truzzi, Anna; Bornstein, Marc H.; Senese, Vincenzo P.; Shinohara, Kazuyuki; Setoh, Peipei; Esposito, Gianluca (Frontiers in Physiology, 2017)
Adults’ adaptive interactions with intimate partners enhance well-being. Here we hypothesized that adult males’ physiological responses to opposite-sex conspecifics’ distress result from an interaction between an environmental factor (early social interaction with caregivers) and a genetic factor (a polymorphism within the promoter region of the serotonin transporter gene, 5-HTTLPR). We assessed heart rate changes in 42 non-married male adults to distress vocalizations (female, infant, and bonobo cries). Males’ early interaction with parents was assessed using the Parental Bonding Instrument. Buccal mucosa cell samples were collected to assess their 5-HTTLPR genotype. A significant interaction emerged between early experience and genetic predisposition. Males with a genetic predisposition for higher sensitivity to environmental factors showed atypical physiological responses to adult female cries according to their experienced early maternal parenting. Environmental experiences and genetic characteristics are associated with adult males’ physiological responses to socially meaningfully stimuli. Understanding the mechanisms that modulate responses to opposite-sex conspecifics may improve personal well-being and social adaptiveness.